Kontribusi Koordinasi Mata dan Tangan dengan Power Otot Lengan Terhadap Hasil Passing Atas Dalam Permainan Bolavoli - Maolana, Surya; Sudrazat, Adang; Rezha, Mohamad (Jurnal Keolahragaan, 2024)
Eye and hand coordination accompanied by arm power is looking for a relationship with overhead passing which is the aim of the research. Correlational design was used as a method for this research. SMK Negeri 1 Rancah is the place for data collection. The author took 20 volleyball extracurricular students. The method for recruiting students is total sampling. The author uses measuring tools, namely eye and coordination tests, press-ups, and overhead passes. The results of the data in the field were analyzed using SPSS series 26. The author's hypothesis was successful, namely: 1. Arm power has a significant relationship with passing technique in volleyball. 2. Eye and hand coordination has a significant relationship with top passing technique in volleyball. 3. Arm power and hand-eye coordination have a greater relationship with overhead passing. Conclusion: Arm power and hand-eye coordination have a greater relationship with top passing in volleyball. Suggestion: It is hoped that as one of the recommendations, the three tests in this study can be used as a test of the physical condition of the sport of volleyball.Koordinasi mata dan tangan disertai dengan power lengan adalah mencari keterkaitan dengan passing atas merupakan tujuan dari penelitian. Corelational design dijadikan cara penelitian ini. SMK Negeri 1 Rancah adalah tempat untuk pengambilan data. Penulis mengambil siswa ekstrakurikuler bolavoli sebanyak 20 siswa. Cara perekrutan siswa yaitu total sampling. Penulis menggunakan alat ukur yakni tes koordinasi dan mata, press-up, dan passing atas. Hasil data di lapangan dianalisis dengan SPSS seri 26. Hipotesis penulis berhasil yaitu: 1. Power lengan memiliki hubungan dengan teknik passing cukup besar pada olahraga bolavoli. 2. Koordinasi mata dan tangan memiliki hubungan dengan teknik passing atas cukup besar pada olahraga bolavoli. 3. Power lengan dan koordinasi mata dan tangan memiliki hubungan yang lebih besar dengan passing atas. Kesimpulan: Power lengan dan koordinasi mata dan tangan memiliki hubungan lebih besar dengan passing atas pada olahraga bolavoli. Saran: Diharapkan sebagai salah satu rekomendasi ke-tiga tes pada penelitian ini dapat dijadikan tes kondisi fisik cabang olahraga bolavoli.